Alterations in the sucrose content and texture of Carica papaya var. California L. and Musa paradisiaca var. formantipyca L. as ripen - Saputri, Dwijowati Asih; Ulmillah, Aulia; Winandari, Ovi Prasetya; Handayani, Fitri (Univeritas Papua, 2024)
Changes in texture and sucrose content in California papaya and kepok bananas after harvest due to metabolic processes can reduce the quality of the fruit. This research investigated the changes in sucrose content and texture during the maturation process of California papayas and kepok bananas. The observed parameters included physical properties, such as texture variations and sucrose levels in the fruit. The research followed a qualitative approach. The research results are described descriptively. This study showed a change in the texture of the kepok banana and California papaya in the ripening process. Changes in the texture of kepok bananas decreased from 3.66 kg/cm on day 2 to day 12 after harvesting from 3.66 kg/cm to 0.56 kg/cm. California papayas from 3.63 to 1.36 kg/cm2. California papayas from 3.63 to 1.36 kg/cm2. The highest sucrose content in the ripening process occurred in kepok bananas and California papayas, respectively, at 0.45? Brix on day 12 and 11.38? Brix on day 10.